2009
DOI: 10.1002/ajhb.20901
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of physiological variables in aged and young women during and following submaximal exercise

Abstract: Previously, we have examined how aging affects the physiological responses of men to endurance exercise. In the present investigation, we aimed to extend our assessment of the influence of aging on exercise-induced responses by focusing on women. Ten young (20.3 +/- 0.3 years; mean +/- SE) and 10 aged (75.5 +/- 1.2 years) women performed 30 min of cycling at 60-65% of their predetermined peak oxygen uptake. Data for respiratory exchange ratio (RER), heart rate, blood pressure, rectal temperature, and plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In those studies it was established that among men the impact of aging is most apparent not during exercise, but rather during postexercise recovery (Deschenes et al, ). In contrast, when examining women, we found that the effects of aging on physiological responses are manifested during, rather than after exercise (Deschenes et al, ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In those studies it was established that among men the impact of aging is most apparent not during exercise, but rather during postexercise recovery (Deschenes et al, ). In contrast, when examining women, we found that the effects of aging on physiological responses are manifested during, rather than after exercise (Deschenes et al, ).…”
Section: Discussionmentioning
confidence: 63%
“…After receiving a full description of the project and its potential risks, all participants provided written informed consent. It should be noted that some of the aged female subjects volunteering for this investigation also participated in an earlier study conducted in our laboratory (Deschenes et al, ). All experimental procedures were approved beforehand by the appropriate Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation